TIME AS A FACTOR IN DETERMINING DEBT-PAYING ABILITY. - Woodbridge, F. W. (The Accounting Review, 1939)
In this article, the author tries to examine time as a factor in determining debt-paying ability. This consideration has led on to other related problems and considerations, and finally to a certain amount of experimental research in debt payment. It has seemed that in the great majority of cases the focal point of business mortality is the actual or prospective inability of a concern to pay its debts. If this simple hypothesis be accepted it seems that the financial health of a business may be measured in terms of the distance that a concern is from this focal point of mortality. As a corollary it would also seem that definite evidence of financial ill health is indicated when a business is unable to pay its debts when they are due. The author reports that in the great majority of cases even the most rigorous classification of current assets and current liabilities fails to reveal whether a business can actually pay its short-term debts when they are due because it does not indicate whether the realization of assets will be sufficiently rapid to meet the agreed liquidation dates of the liabilities.